ESTIMATING THE RELATIONSHIP BETWEEN GOVERNANCE, ECONOMIC GROWTH, INEQUALITY AND POVERTY - TOUITOU, Mohammed (Theoretical and Practical Research in Economic Fields; Vol 12 No 1 (2021): TPREF, Volume XII, Issue 1(23), Summer 2021DO - 10.14505/tpref.v12.1(23).03, 2021)
The main purpose of this paper is to estimate the relationship between governance, economic growth, inequality and poverty for 81 countries for the period 2000-2016. We divided the countries into three groups, low-income countries, lower-middle-income countries and upper-middle-income countries. To answer our research question, we use a structural model with simultaneous equations on Panel data. Our results show that the positive or negative impact of governance on the growth-inequality-poverty triangle changes depending on the dimension of governance taken into account and the sample being studied. Given the negative relationship between inequality and growth, democracy should a second time positively affect economic growth through the reduction of inequalities.